2014
DOI: 10.2399/ana.14.040
|View full text |Cite
|
Sign up to set email alerts
|

Plastination: basic principles and methodology

Abstract: Plastination is the method of long term preservation of the biological tissues with completely visible surface and high durability. The plastinates are devoid of harmful effects of formalin and they serve as excellent teaching tools in education. Additionally, plastination is an outstanding tool to study cross-sectional anatomy. The three major methods used in plastination are silicone plastination, sheet plastination with epoxy method and sheet plastination with polyester method. Silicone plastination is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 4 publications
1
13
0
Order By: Relevance
“…Silicone plastination (S-10 technique) is one of the simplest and most versatile types of plastination involving silicone polymers as impregnation mixtures and hardeners. Among different silicone polymers used, S-10 (polydimethylsiloxane) is the most popular and widely used polymer and results in more natural-looking, opaque specimens [17][18][19]. The S-10 technique is comprised of four plastination steps, namely fixation, dehydration, forced impregnation, and curing.…”
Section: Plastinationmentioning
confidence: 99%
“…Silicone plastination (S-10 technique) is one of the simplest and most versatile types of plastination involving silicone polymers as impregnation mixtures and hardeners. Among different silicone polymers used, S-10 (polydimethylsiloxane) is the most popular and widely used polymer and results in more natural-looking, opaque specimens [17][18][19]. The S-10 technique is comprised of four plastination steps, namely fixation, dehydration, forced impregnation, and curing.…”
Section: Plastinationmentioning
confidence: 99%
“…This is a method or technique used for the long term preservation of body or part of body [8]. This technique was established by German scientist Gunther von Hagens in 1977 [9] in laboratory of Heidelberg University [10].…”
Section: Plastinationmentioning
confidence: 99%
“…Silicone plastination is one of most common techniques of plastination which can be used for body, organs, part of organ and slices [8] (Figure 3). The Plastination techniques depend on vacuum of original body or tissue fluid and replace it by special curable polymer of the standard silicone S-10 [9].…”
Section: A) Silicone Plastinationmentioning
confidence: 99%
“…Adaptation to the cross‐sectional anatomy may cause anxiety in the students learning anatomy with a traditional approach due to the fact that it requires to figure out and comprehend the structures beyond systematic anatomy. Thus, it is recommended to acquire new and various tools according to the developing technology (Ghosh, 2015; Sargon & Tatar, 2014). It is suggested that plastination is one of the best preservation methods for cross‐sectional anatomic structure (Siddiquey et al, 2009).…”
Section: Discussionmentioning
confidence: 99%